Case Study Of Standard Nutrition Care Process Of Hypertensive Heart Disease Patients in Pavilion Seroja at Undata Regional Hospital Palu Central Sulawesi Province: Studi Kasus Proses Asuhan Gizi Terstandar pada Pasien Hypertensive Heart Disease di Paviliun Seroja RSUD Undata Palu Provinsi Sulawesi Tengah - Fahmi Hafid; Wery Aslinda; Nanda Dea Rizki; Adhyanti Adhyanti (Poltekkes Kemenkes Palu, 2021)
Hypertension is a disease that requires a standardized nutritional care process (NCP). This is because hypertension can become an advanced and chronic disease that has a serious impact on the health of the body, causing complications. This study aims to perform NCP on hypertensive patients in the Seroja Pavilion class II UPT. Undata Hospital Palu. This study is a review of research with a case study approach (Case Study), with samples 1, and was diagnosed with Hypertensive Heart Disease (HHD). The data collected were anthropometry (weight and height), food intake, food habits, client history, socio-culture, biochemical examination results, and physical/clinical examination. The data collection technique is obtained from primary data which is collected directly from the patient and the patient's family, and secondary data is obtained through the patient's medical record. The results showed an increase in the patient's food intake, namely 88.0% energy, 113.4% protein, 48.3% fat, and 95.5% carbohydrates, no change in body weight, and an increase in nutritional knowledge. Diagnoses at the start of the study included NI-2.1, NI-5.4, NC-2.2, NB-1.1 until at the end of the study being N-2.1 and NI-5.4. The interventions given included Low Salt Diet III, soft food form, 3 times main meal frequency, 2x interlude, with oral route. In conclusion, there were changes in intake, physical/clinical as well as knowledge/attitudes of patients on hypertension that had been given NCP.